Basic Life Support Training as Mandatory Training in Educational Institutions to Deal with Emergencies - Munazza Suharwardy Obaid; Saeed Minhas; Fouzia Naeem Effendi; Shiraz Shaikh; Farah Fatima Abbas; Ferrukh Zehravi; Malik Tajuddin; M. Bastle Ullah Ansari (ziauddin University, 2024)
Background: Injury is a significant issue of public health, a major global burden and first aid training programs incorporated as part of school curriculum will have a considerable impact on public health, and this will in turn reduce out of hospital cardiac arrests. The study aimed to determine the immediate First aid knowledge and long term retention of its knowledge (after three months) of the students (13-18 years), participating in a volunteer program in Karachi. Methods: This study was conducted in a tertiary care hospital, delivering First aid training to 143 participants by Basic life support (BLS) trained staff in a tertiary care hospital. The design consisted of a pre-test, post-test and follows up assessments, carried out via questionnaire and hands-on assessment. SPSS was used for statistical analysis. ANOVA and Friedman test was applied to evaluate the dependent variable's improvement in knowledge between pre, post and follow up tests. Results: From 143 participants, 41.5 %, 63.8 % and 61 % satisfactory results were seen in the pre-test, post-test and follow up assessments, respectively. In Pre-test, males scored 18.75 % and the females scored 8.42%, whereas, in the post-test, the scores were 75.7% and 64.58% respectively. Similarly, in follow up evaluations results obtained were 62.1% and 45.8% respectively. Hands-on scores were 88.4% in males and 95.8 % in females. Conclusion: The level of first aid knowledge was unquestionably less satisfactory in the pre-test evaluations compared to post-test and follows up assessments. Due to its effectiveness, it should be incorporated as part of the school curriculum. Keywords: Adolescents; Knowledge; Cardiopulmonary Resuscitation.